The house of Thulare :The problem of succession and the split of the Bapedi Nation, 1824-1884 - Ramushu, Mafori Charles (My University, 2007)
Refer to document
Thesis (M.A. (Folklore)) --University of Limpopo, 2007
Keywords: Succession; 968.04000968; Kings and Rulers